2020
DOI: 10.3390/cancers12040914
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapeutic Activity of Davallia formosana on Prostate Cancer Cells through Coordinated Blockade of Lipogenesis and Androgen Receptor Expression

Abstract: Background: Prostate cancer (PCa) is the most prevalent malignancy diagnosed in men in Western countries. There is currently no effective therapy for advanced PCa aggressiveness, including castration-resistant progression. The aim of this study is to evaluate the potential efficacy and determine the molecular basis of Davallia formosana (DF) in PCa. Methods: LNCaP (androgen-sensitive) and C4-2 (androgen-insensitive/castration-resistant) PCa cells were utilized in this study. An MTT-based method, a wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In PCa, the ethanol extract of Ganoderma tsugae, a Chinese natural and herbal product, significantly inhibits the expressions of SREBP-1 and its downstream genes associated with lipogenesis and downregulates the levels of AR and PSA to block cancer growth and progression with androgen response and castration resistance ( 172 ). The results from the in vitro and in vivo experiments demonstrated that the ethanol extract of Davallia formosana can suppress proliferation, migration, and invasion in PCa cells by inhibiting the levels of SREBP-1, FASN, AR, and PSA, suggesting that SREBP-1/FASN/lipogenesis and the AR axis could be potential targets for the treatment of PCa ( 173 ). The cell suspension culture extract from Eriobotrya japonica significantly inhibits PCa cell growth, migration, and invasion by decreasing the SREBP-1/FASN-mediated lipid metabolism and AR signaling pathway in the cell and mouse models ( 174 ).…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…In PCa, the ethanol extract of Ganoderma tsugae, a Chinese natural and herbal product, significantly inhibits the expressions of SREBP-1 and its downstream genes associated with lipogenesis and downregulates the levels of AR and PSA to block cancer growth and progression with androgen response and castration resistance ( 172 ). The results from the in vitro and in vivo experiments demonstrated that the ethanol extract of Davallia formosana can suppress proliferation, migration, and invasion in PCa cells by inhibiting the levels of SREBP-1, FASN, AR, and PSA, suggesting that SREBP-1/FASN/lipogenesis and the AR axis could be potential targets for the treatment of PCa ( 173 ). The cell suspension culture extract from Eriobotrya japonica significantly inhibits PCa cell growth, migration, and invasion by decreasing the SREBP-1/FASN-mediated lipid metabolism and AR signaling pathway in the cell and mouse models ( 174 ).…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…[84] Davallia divaricata extract targets the sterol regulatory element-binding protein 1 (SREBP-1)/ fatty acid synthase (FASN)/Lipogenesis and AR axis, providing a new molecular basis for its use in PCa treatment. [85] Ganoderma tsugae extract suppresses cell growth and progression by blocking the SREBP-1/AR axis and activating the caspase-dependent apoptotic pathway in PCa cells. [86] The spore oil of Ganoderma lucidum downregulates AR function and transcriptional activity in androgen-dependent PCa cells, contributing to the inhibition of LNCaP cell growth.…”
Section: Inhibitory Effects Of Chm On Ar In Pcamentioning
confidence: 99%
“…Ginsenoside Rh2, an extract from ginseng, reverses cyclophosphamide-induced immunodeficiency in non-small cell lung cancer by inhibiting the expression of SREBP1 and its nuclear translocation and affecting the interaction of SREBP1 with FASN ( Qian et al, 2019 ). Davallia formosana ethanol extract inhibits proliferation, migration, and invasion in prostate cancer cells by inhibiting the expression of SREBP1 and FASN and reducing the expression of AR and prostate-specific antigen (PSA) ( Hsieh et al, 2020 ). Curcumin, the yellow pigment from turmeric, exhibits anti-cancer and antioxidant effects, especially in hepatocarcinoma.…”
Section: Treatment In Cancermentioning
confidence: 99%